A chemical investigation of Cassia alata L. (Fam. Leguminosae) - Villarroya, Maria Luisa E.
Compounds I to VI were isolated from Cassia alata L. by column chromatography. Compounds I to IV were found to be chrysophanol, emodin, rhein and aloe-emodin, respectively by TLC, melting point determinations, UV and IR spectral analyses. Compound V was found by TLC using a different solvent system to be a mixture. Compound VI, C35 H58 O6, m.p. 277-8 (CHCl3-MeOH) and with an acetate derivative melting at 164-5(degrees), was identified as a sitosterol glycoside with two conjugated double bonds in the tetracyclic moiety by UV, IR, NMR and mass spectral analyses.